Contribution Of Psychological Well-Being to Online Self Presentation in Active Instagram User Students - Annamori, Aida (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
This study aims to examine the contribution of psychological well-being to online self-presentation in students who are active Instagram users. The subjects of the study consisted of 276 students who are active Instagram users in Padang City. The sampling technique used in this study was purposive sampling. Determination of the number of samples in this study used the Isacc and Michael formula approach. Data analysis using simple linear regression techniques showed that students who are active Instagram users in Padang City tend to have high levels of psychological well-being and high online self-presentation. The results of this study also found that there was a contribution of psychological well-being to the aspects of false self, real self, and ideal self in the online self-presentation variable in students who are active Instagram users. And the results of this study showed a positive and significant influence between psychological well-being and false self with a contribution of 15.8%, real self of 6.7%, and ideal self of 9.3% in students who are active Instagram users.